Predictive models of instantaneous maximum discharges forcatchments of mountainous environments, supported by morphometric parameters - Méndez, Williams; Córdova, José; Bravo, Lelys (Rev. Téc. Fac. Ing. Univ. Zulia, 2015)
The instantaneous maximum discharge is a hydrological parameter that can be estimated by deterministic, probabilistic and empirical models or direct instrumental measurements, however, their magnitudes are influenced equally by the morphometry of the catchment and its drainage network. Is purpose of this research to explain the relationships between the instantaneous maximum discharges of catchments of “El ívila” Massif northern hillside (Vargas State, Venezuela) and the morphometric parameters of these, to propose predictive models of such responses. The methodology consisted of measurements and calculations of the morphometric parameters of the catchments and their drainage networks, and the use of multivariate statistical techniques (linear correlation analysis, principal component analysis and multiple linear regression analysis). It was considered as instantaneous maximum discharges for a return period of 100 years those estimated by other authors. Most of the predictive models generated by each morphometric variable shows very good results in their estimates of the instantaneous maximum discharges of the catchments analyzed, however, only one was selected as the best predictor model (best correlation coefficients), which in this case is the corresponding variable basin scale.